Kaderisasi Ulama di Sumatera Utara: Antara Pesantren dan Pendidikan Kader Ulama (PKU) - Napitupulu, Dedi Sahputra; Asari, Hasan; Arsyad, Junaidi (FIKRAH, 2023)
This study aims to analyze the regeneration of ulama in North Sumatra carried out by pesantren and Pendidikan Kader Ulama (PKU). This research uses the literature study method by collecting written sources in the form of authoritative books and journals. The theory used in this study is the theory put forward by Azyumardi Azra, that the function of pesantren in the past was the transmission and transfer of Islamic sciences, preserving Islamic traditions, and being a place to reproduce ulama. Currently, there seems to have been a shift towards the theory that pesantren can no longer be expected as a forum for cadre ulama, so the alternative solution is to establish an independent clerical cadre institution. The results of this study show that there is currently a scarcity of ulama. Many pesantren that once functioned as appropriate reproducing ulama can no longer be expected because they have been contaminated with the current of modernization. Pesantren can reformulate the curriculum as before and also it can develop Ma'had 'Aly. PKU is an alternative solution that can be used as an effort to regenerate ulama. Then, another important thing is that the mastery of the yellow book for prospective ulama must be strengthened because it is an absolute qualification for ulama. The real contributions from this research are to provide recommendations for pesantren to reinstate their original function, namely producing clerical cadres. Then, the efforts to regenerate ulama must be supported by Islamic mass organizations as a legacy of ulama which are also responsible for establishing clerical regeneration institutions.